Marketingový mix společnosti Alcon - Svobodová, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tématem diplomové práce je rozbor společnosti Alcon Pharmaceuticals Czech Republic s.r.o., zabývající se prodejem a výrobou přípravků pro oční péči, na základě marketingového mixu. Mým cílem je pomoci zkvalitnit péči o stávající zákazníky a najít nejvhodnější kombinaci prostředků, které povedou k získání klientů zcela nových. Ve své práci se zaměřuji převážně na divizi CLC (Contact Lenses Care).

The theme of this thesis is an analysis of Alcon Pharmaceuticals Ltd. Czech Republic, engaged in the sale and manufacture products for eye care on the basis of the marketing mix. My goal is to help improve the care of existing customers and find the best combination of funds that will lead to entirely new customer acquisition. In my work I focus mainly on the division of CLC (Contact Lenses Care).
Marketing Mix of Company Alcon
Keywords: Marketingový mix; marketing; reklama; komunikace; swot analýza; konkurence; zákazník; cíl; Marketing mix; Marketing; promotion; communikation; swot analysis; competition; customer; target